The knowledge and awareness on research methodology among dentists in Telangana region, India - J Vijay Kumar; Venkat Baghirath Pacha; Yashovardhan Naishadham (Wolters Kluwer Medknow Publications, 2016)
Introduction: In this era of scientific advancement, research is vital and forms the heart of the knowledge expansion. Dentistry is one the fastest evolving branches of science in today's world and needless to say, it is centered on research. In India, research is a part of postgraduate curriculum. Many research works are conducted by postgraduates as a necessity, but very few do it with actual interest. Hence, in this study, we plan to conduct a survey on the awareness of dentists toward research in Telangana region. Aim: To assess the knowledge and highlight the need to learn research methodology for dentists in Telangana region. Materials and Methods: A cross-sectional questionnaire study was conducted with 15 close-ended questions to know different ideologies among dentists for planning a research and to correlate opinions from dentists of various regions of Telangana state. A total of 115 participants took part in the study. They gave their consent for the study and gave their opinions with their free will. We categorized our results according to the designation of the participants and the answers that were given for each question. Statistical analysis was performed using SPSS version 22. Results: A statistically significant difference (P < 0.05) of opinions was obtained with regards to the type of study that was preferred, type of analysis that was done, and obtaining a statistically significant value for their results. Conclusion: There is considerable variation when it comes to planning minor steps of study with few basics being overlooked. There is a need for establishing a standardized protocol for planning a study.